Barriers and Facilitators of Occupational Performance of People With Stroke: A Meta-synthesis - Hassan vahidi; Ghazaleh Mandani; Seyed Ali Hosseini; Nazila AkbarFahimi; Azad Rahmani (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Strokes are among the most destructive health problems. They can especially have detrimental effects on the occupational performance of sufferers. The experiences of patients suffering from stroke regarding the impact of the disease on their occupational performance, especially the barriers and facilitators of this performance, can help understand this phenomenon better and design client-centered interventions in this field. Nevertheless, a limited body of literature has investigated the encounters of these individuals and their familial caretakers within this domain. Therefore, the objective of this research is to synthesize the available research evidence regarding the experiences of stroke survivors and their family caregivers regarding barriers and facilitators of occupational performance after stroke. Materials & Methods All published articles were searched from 4 databases without a time limit according to the determined keywords. Among the 70 articles found, only 22 were included in the study and analyzed based on the quality indicators. Results The analysis of extractive studies led to the emergence of two categories of barriers to occupational performance with subcategories of individual obstacles, contextual barriers, and rehabilitation barriers and facilitators of occupational performance with subcategories of educational strategies, development of environmental support, and strengthening of individual strategy.  Conclusion Clients with stroke have many barriers in their occupational performance, and the barriers that are related to the context of rehabilitation are significant. In addition to these important barriers, the existence of supportive and educational facilitators can help improve the client's occupational performance. A better understanding of the factors related to the occupational performance of patients suffering from stroke requires more studies, especially in the relationship between the context and professional issues of occupational therapy and clients' occupational performance.